1972
DOI: 10.1007/bf01298413
|View full text |Cite
|
Sign up to set email alerts
|

Unzerlegbare Darstellungen I

Abstract: Let K be the structure got by forgetting the composition law of morphisms in a given category. A linear representation of is given by a map V associating with any morphism ~ : a -~e of K a linear vector space map V(~) : V(a) -~V(e). We classify those K having only finitely many isomorphy classes of indecomposable linear representations. This classification is related to an old paper by Yoshii [3].i. Einleitung.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
587
0
25

Year Published

1987
1987
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 745 publications
(615 citation statements)
references
References 1 publication
3
587
0
25
Order By: Relevance
“…A quiver is, by definition, a directed graph. A representation of the quiver is given (see [6], and also [2,14]) by assigning to each vertex a vector space and to each arrow a linear mapping of the corresponding vector spaces. For example, the quivers 1 e e 1 * * 4 4 2 1 9 9 e e correspond respectively to the problems of classifying:…”
mentioning
confidence: 99%
“…A quiver is, by definition, a directed graph. A representation of the quiver is given (see [6], and also [2,14]) by assigning to each vertex a vector space and to each arrow a linear mapping of the corresponding vector spaces. For example, the quivers 1 e e 1 * * 4 4 2 1 9 9 e e correspond respectively to the problems of classifying:…”
mentioning
confidence: 99%
“…It is finite-dimensional iff the quiver has no oriented cycles. Gabriel [24] has shown that the quiver algebra of a finite quiver has only a finite number of k-finite-dimensional indecomposable modules (up to isomorphism) iff the underlying graph of the quiver is a disjoint union of Dynkin diagrams of type A, D, E.…”
Section: 7mentioning
confidence: 99%
“…An algebra A is of finite representation type if the category ind A admits only a finite number of pairwise nonisomorphic modules. It is well known that a hereditary algebra A is of finite representation type if and only if A is of Dynkin type, that is, the valued quiver Q A of A is a Dynkin quiver of type A n (n 1), B n (n 2), C n (n 3), D n (n 4), E 6 , E 7 , E 8 , F 4 and G 2 (see [8], [9], [10]). A distinguished class of algebras of finite representation type is formed by the tilted algebras of Dynkin type, that is, the algebras of the form End H (T ) for a hereditary algebra H of Dynkin type and a (multiplicity-free) tilting module T in mod H. An algebra A is called selfinjective if A A is an injective module, or equivalently, the projective modules in mod A are injective.…”
mentioning
confidence: 99%